Skeletal muscle metastasis of early glottis laryngeal carcinoma: a case report - Fatima Shaukat; khan, Durria; Ahmed, Yumna; Hashmi, Syed Furqan Ahmed; Mahmood, Tariq (Journal of the Pakistan Medical Association, 2025)
Glottis cancer, a prevalent subtype of laryngeal malignancies, is frequently encountered in clinical practice in LMIC (Lower Middle Income Countries). This case report presents an extraordinary occurrence of T1 glottis cancer, shedding light on a rare clinical scenario. Typically, early-stage glottis cancers, including T1 tumours, exhibit a remarkable rarity of occult lymph node involvement, with estimates indicating a prevalence of less than five percent. However, in this significant case, seen at the Cyberknife and Tomotherapy Centre, Jinnah Postgraduate Medical Centre (JPMC), Karachi, in 2022, the patient faced a recurrence of the disease, manifesting within the sternocleidomastoid muscle—a highly unusual presentation. Notably, this recurrence occurred without any discernible involvement of cervical nodes or primary site, i.e. larynx. Keywords: Glottic, Carcinoma, Radiation, Skeletal metastasis.